Poetics, creative processes and the research journal of the painter in training (Revista Apotheke, 2020)
This article deals with what we consider to be poetics, clarifying the importance of understanding this concept in teaching and the methodology applied to practical studio subjects, in the Basic Cycle of UFRJ’s - Federal University of Rio de Janeiro - Painting Course, School of Fine Arts. This designation, which covers so many possible concepts in the artistic field, is fundamental in deepening the work of an aspiring research artist in painting. The artist is a person who thinks, proposes and transforms his culture and society through a language. That is why it is important to be aware of your poetic field, as it is what drives research, creative act and expression. The poetics that a painting student creates and develops works as the main catalyst for his production, guiding the creative process, imagination and expression. In addition to addressing this concept, we will present here the teaching methodology applied to the classes of second and third periods of the Painting course. This proposes, through the elaboration of a cluster of images and artist documents of the most varied types, the organization of creative thinking in research journals, also called sketchbooks. These supports are like receptacles that simultaneously promote learning, research and creation of students initiated in this complex, rich and ancestral language: painting.
Keywords: painting; poetic; creative process; methodology; sketchbook